How the vertical gradient of light in the understorey and water seasonality affect leaf traits of Vanilla phaeantha (Orchidaceae), a crassulacean acid metabolism (CAM) hemiephyte - Buss, Aldineia; Silva, Wesley Costa; Costa, Vladimir Eliodoro [UNESP]; Moreira, Ana Silvia Franco Pinheiro (CSIRO Publishing, 2024)
Structural and physiological leaf traits and their plasticity were compared in the hemiepiphyte Vanilla phaeantha. This species grows along a phorophyte reaching different understorey positions and exhibiting diverse responses to environment changes. We analysed three height strata above the ground, establishing a light gradient, and considering seasonal water fluctuations. The upper leaves had higher area and mass and were less pigmented. The dry season induced a reduction of approximately 2 h of stomatal opening over the diel 24 h crassulacean acid metabolism (CAM) cycle in the leaves at all understorey positions. The leaves more exposed to sunlight were larger with higher titratable acidity during the rainy season, while the leaves near the ground maintained the same rates of stomatal conductance and nocturnal acidification between seasons, with lowest values of carbon isotopes in the rainy season. Our research showed that some structural leaf traits (such as specific leaf mass, biomass, and saturated water content) are sensitive to variation in understorey position. In contrast, other physiological traits (stomatal conductance, transpiration, and fluorescence parameters) are more sensitive to seasonal variations. The results are a novelty in assessing the variation of CAM along the same plant in a height gradient and under field conditions.
Keywords: CAM plants; epiphytes; leaf development; leaf plasticity; orchids; photosynthesis; understorey heterogeneity; water relations